Odpowiedzi

2010-03-03T16:20:53+01:00
Najlepsza Odpowiedź!
2010-03-03T16:31:29+01:00
A/x+2y=9
y-1=3x
b/x-y=2
1/2x-1=1/4y
c/-x-y=2
2(3x+y)=-20
d/4x+3y=54
1/3x=4(1+1/8y)

a) x+2y=9
y-1=3x

x=9-2y
y-1=3x
y-1=3*(9-2y)
y-1=27 - 6y
y+5y=27+1
6y=28 /:6
y=4 4/6
x=9-2*4 4/6
x=9-9 2/6
x=2/6

b) x-y=2
1/2x-1=1/4y

x=2+y
1/2*(2+y) - 1 = 1/4y
1+1/2y - 1 = 1/4y
1/2y-1/4y=0
y=0
x=2+0
x=2

c) -x-y=2
2(3x+y)=-20

-x=y+2
6x+2y=-20
x=-y+2
6*(-y+2)+2y=-20
-6y+12+2y=-20
-4y=-20-12
-4y=-32
y=8
x=-8+2
x=-6

2010-03-03T16:32:12+01:00
A)
x+2y=9
y-1=3x
x+2y=9/-2y
y-1=3x
x=9-2y
y-1=3*(9-2y)
y-1=27-6y/+1
y=28-6y/+6y
7y=28/:7
y=4
x=9-(2*4)
x=1